ANALISIS TEORI POINCARE VS FREUD (Bimbingan Belajar Pada Anak Tuna Grahita Ringan) - Ahmad Syamsul Muarif (Jurnal At-Taujih, 2022)
The problem to be discussed in this study is that low IQ children have difficulty understanding abstract things, poor concentration, poor experience, lack of initiative, forgetting and difficulty in calculating complicated numbers. The purpose of this article is to analyze and compare the opinions of Henri Poincare with Sigmun Freud which is suitable for use in guiding and providing counseling to children who have low IQ. The method used in this study is qualitative with a library research approach, with data obtained from books and journals. The results of a comparative study between Freud's Psychoanalysis and Poincare's geometry are very contradictory, because the client is suffering from a low IQ, which does not require problems as a reference in analyzing himself, but students or children who have a low IQ can be given material or math problems that easily repeats itself so that his memory gets used to it. In his theory Poincare is called the result of intuition itself.